1980
DOI: 10.1071/ch9801335
|View full text |Cite
|
Sign up to set email alerts
|

The Meisenheimer rearrangement in heterocyclic synthesis. III. Derivatives of the 1H-[1,2]oxazepino[6,5-b]indole, thieno[2,3-e][1,2]oxazepine and [l]benzothieno[3,2-e][1,2]oxazepine ring systems

Abstract: The new heterocyclic derivatives 3-methyl-1-phenyl-3,4,5,10-tetrahydro- 1H-[1,2]oxazepino[6,5-b]-indole (5c), 6-methyl-4-phenyl-4,6,7,8- tetrahydrothieno[2,3-e][1,2]oxazepine (6f), and 3-methyl-1-phenyl- 1,3,4,5-tetrahydro[1]benzothieno[3,2-e][1,2]oxazepine (7c) were prepared in good yield by thermal Meisenheimer rearrangement of the corresponding tertiary amine N-oxide precursors. No such rearrangement occurred on heating the N-oxides of the fused bicyclic systems 2,3,11,12-tetramethoxy-5,8,9,13b-tetrahydro-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…2 2 Inspection of the literature showed a TCfC conformation for the (")-8,9-dimethoxy-3-methyl-l-phenyl-3,4,5,6-~tr~ydro-lH-2,3-benzoxazocine (8) free base. 23 The phenyl ring occupies a similar exo-orientation on the 2,3-and 2,5benzoxazocine rings, as shown by X-ray-determined structures for 1, 6, 7, and 8 Methyl group substitution of the equatorial (pro-R) C(3)proton was expected to afford a stabilized nefopam TCfC conformation similar to that noted for TCfC (1S,3R)-8 IX-ray crystallography shows the N(31-methyl group to be equatorially oriented in TCfC (1S,3R)-8]. Preliminary molecular mechanics calculations suggested that appropriate C-methyl substitution of the nefopam 2,5-benzoxazocine ring could result in solution-state stabilization of the TCfC conformation.…”
Section: M) In Thementioning
confidence: 99%
“…2 2 Inspection of the literature showed a TCfC conformation for the (")-8,9-dimethoxy-3-methyl-l-phenyl-3,4,5,6-~tr~ydro-lH-2,3-benzoxazocine (8) free base. 23 The phenyl ring occupies a similar exo-orientation on the 2,3-and 2,5benzoxazocine rings, as shown by X-ray-determined structures for 1, 6, 7, and 8 Methyl group substitution of the equatorial (pro-R) C(3)proton was expected to afford a stabilized nefopam TCfC conformation similar to that noted for TCfC (1S,3R)-8 IX-ray crystallography shows the N(31-methyl group to be equatorially oriented in TCfC (1S,3R)-8]. Preliminary molecular mechanics calculations suggested that appropriate C-methyl substitution of the nefopam 2,5-benzoxazocine ring could result in solution-state stabilization of the TCfC conformation.…”
Section: M) In Thementioning
confidence: 99%
“…is non-hom ologous seven member ring that contains two heteroatoms (Oxygen and Nitrogen). Oxazepines (serax) is used as antibiotics, enzyme inhibitors, pharmacological interest, and it has been studied much chemically [18][19][20][21] and biological studied [22][23][24][25][26] Diazepam (valium) is a class of drugs used as relaxants, minor tranquilizers, hypnotics and muscle relaxant because it is often seen in fortensic and clinical cases. It introduced in 1969 under brand name valium ( [27][28][29]Diazepam (valium) is used to relief anxiety tension associated with anxiety disorder and muscle spasms as well as alcohol withdrawl [24] and other clinically uses [25,26] [35] In agriculture tetrazoles serve as plant growth regulators, as herbicides and as fungicides.…”
Section: Introductionmentioning
confidence: 99%
“…Wissam [3] has synthesized thiadiazole fused with triazole ring 3-(p-bromo phenomethyl)-5-mercapto-5triazole [3,4-b]-1,3,4-thiadiazole by using CS 2 and KOH.1,3,4-thiadiazoles are known for their broad-spectrum of biological activity such as antifungal [4,5] antibacterial [6] herbicidal [7] antiviral [8] and analgesic effect [9,10] 2-benzylamino-5-(2pyridyl)1,3,4-thiadiazole used as antibactrial agent([11] Aromatic Schiff's base is considered as a chromophore due to conjucation of the electron pair on the nitrogen atom with the benzene ring of aniline and benzaldehyde [12] Biologically, Schiff's bases are important since they have biological activity against bacteria and fungi [13][14][15][16] Oxazepam (serax) is a new benzodiazepine derivative introduced in 1965 for use in the relief of the psychoneuroses characterized by anxiety and tension [17] Oxazepam (serax) is non-hom ologous seven member ring that contains two heteroatoms (Oxygen and Nitrogen). Oxazepines (serax) is used as antibiotics, enzyme inhibitors, pharmacological interest, and it has been studied much chemically [18][19][20][21] and biological studied [22][23][24][25][26] Diazepam (valium) is a class of drugs used as relaxants, minor tranquilizers, hypnotics and muscle relaxant because it is often seen in fortensic and clinical cases. It introduced in 1969 under brand name valium ( [27-29]Diazepam (valium) is used to relief anxiety tension associated with anxiety disorder and muscle spasms as well as alcohol withdrawl [24] and other clinically uses [25,26] Thiazepine , many examples belonging to oxazepines, diazepines are documented, but very little is known about thiazepine [30,31]1,4-Benzothiazepine derivatives are of considerable interest because of their biological activity as a muscle relaxants [32,33] Thiazepine is one of the drugs which have biological interest due to their activity on the central nervous system, as enzyme inhibitors, anti-cancer, anxiolytic activity, anticonvulsant, muscle relaxant…”
Section: Introductionmentioning
confidence: 99%